Maithilīśaraṇa Gupta aura Subrahmaṇya Bhāratī : tulanātmaka adhyayana - Nāgalakshmī Nārāyaṇa, 1925- (Mukhya vitaraka Bhāshā Prakāśana, 1978)
On the life and works of Maithili Sarana Gupta, 1886-1964, Hindi poet, and C. Subrahmanya Bharati, 1882-1921, Tamil poet; a comparative study.